Research on Pricing on Re Market in Sevastopol - M. V. Bezhan; I. S. Rakitina; I. A. Shevchuk (Вестник Российского экономического университета имени Г. В. Плеханова)
Affordability of housing is one of the most important and topical trends, that is taken into account in pursuing state economic policy in Russia. Pricing process on RE market acts as a serious factor influencing housing affordability and appeal of certain regions for continuous residence. Construction volumes directly depend on effective demand and conditions of mortgage crediting. The article discusses acute issues of certain factor impact on pricing process on RE market. In order to identify the interconnection of these factors the research conducted econometric assessment of the impact of wage dynamics and mortgage crediting portfolio on changes in market RE cost in the city of federal importance Sevastopol. Methods used in the research: models of vector auto-regression (standard and bias). Data of official statistics were used as an information base, including data of the Bank of Russia, as well as publications by economists. The initial hypothesis of the research said that proposed variables influence seriously the actual figure of housing cost in the region. Econometric analysis of this thesis proved in general the hypothesis. Findings of the research can form a scientific base for forecasting inflation processes on RE market in the city of Sevastopol and can be used in other entities of the Russian Federation.